JAMES BOND AND STIERLITZ IN THE CONTEXT OF “PERSONAL HISTORY” - Dar`ya A. Holub (Alfred Nobel University Journal of Philology, 2019)
The article is devoted to the study of the personal history of superspies from British Intelligence James Bond and the Soviet intelligence officer Stierlitz. The special understanding of the myth with its historical features, which has been developed in the literature by the end of the 20th century, with the obligatory coverage of the repetitive patterns in the life of mankind is emphasized. The phenomenon of the mythologization of popular characters/heroes is considered through the prism of their personal history, formed by J. Semenov and I. Fleming, with the actualization of the foretype for their creation and an attempt to predict the mass reader’s demand for a set of certain qualities and features laid down in the new character. Particular attention is given to Bond and Stierlitz prototypes, prompting the search for real origins of novel characters and thereby creating a protoplast story based on the biography of writers and real figures of intelligent officers. The importance of the appearance of popular characters on the TV screen is emphasized. It is underlined that this process has significantly permeated the literary existence of Stierlitz and Bond, giving impetus to the creation of new stories, video games, jokes and funny stories about spies / intelligent officers among mass readers / viewers. Special perception by the mass audience of spy characters / heroes is stressed: whereas the mission of the 007 agent was to become the new symbol of England, to restore the honour of Britain in the eyes of the whole world – he was supposed to be not just a hero, but a man with extraordinary abilities that was irreconcilable to evil and eventually, could triumph over it, while remaining handsome gentleman conquering women’s hearts; Semenov’s hero did not possess Bond like eye-catching tricks, his main strengths were his ability to stay focused and think a lot, make responsible decisions and defend them to the end, relying only on himself. After difficult victories and bitter disappointments during the last 50 years of the 20th century, the reader needed an understanding of the fact that the romantic hero did exist and could perform a rescue mission. Therefore, the arrival of Isaev-Stierlitz and James Bond was anticipated, new mass characters / heroes were accepted unconditionally. Thus, the emergence of new literary characters in mass literature is perceived as a significant phenomenon of the era of I. Fleming and J. Semenov, and new myths among the mass readers and viewers are generated by their incredible popularity and constant interest in their personalities who have gone far beyond the scope of the novels.